Formaldehyde : exposure, toxicity and health effects - Zhang, Luoping (Royal Society of Chemistry, 2018)
This book consolidates current knowledge of all aspects of formaldehyde from exposure to genotoxicity and from epidemiological case studies to adverse health outcomes.
Includes indexes.
Keywords: Formaldehyde -- Toxicology.; elektronické knihy; electronic books